Loss of TACC2 impairs chemokine CCL3 and CCL4 expression and reduces response to anti-PD-1 therapy in soft tissue sarcoma - Jing Yang; Xiuxia Lu; Qiyan Cai; Mengmeng Liu; Tianliang Xia; Dongchun Hong; Liyuan Le; Xinke Zhang; Xing Zhang (Molecular Cancer)
Abstract Background Soft tissue sarcoma (STS) is a rare, heterogeneous malignancy with limited treatment options for metastatic disease. Despite advances in immunotherapy, including PD-1 inhibitors, clinical outcomes remain suboptimal, highlighting the need for novel biomarkers and therapeutic strategies. This study investigated the role of TACC2 in STS, focusing on its impact on the immune microenvironment and immunotherapy response. Methods Whole-exome sequencing was performed to characterize TACC2-related genomic alterations in STS cohorts, complemented by immunohistochemistry for protein-level validation. Mechanistic insights were obtained through chromatin immunoprecipitation (ChIP) and co-immunoprecipitation assays, focusing on TACC2’s interaction with the NuRD/CoREST complex. The efficacy of anti-PD-1 therapy was evaluated in TACC2-overexpressing mouse models, and clinical relevance was analyzed using patient survival and treatment response data. Results TACC2 acted as a tumor suppressor in STS, with low expression associated with poor overall survival. Mechanistically, TACC2 enhanced CCL3 and CCL4 transcription, promoting CD8 + T cell infiltration by inhibiting NuRD/CoREST nuclear translocation. In vivo, TACC2 overexpression synergized with PD-1 blockade therapy, leading to a significant reduction in tumor volume and prolonged survival. Clinically, high TACC2 expression was associated with improved responses to immunotherapy. Conclusions In conclusion, TACC2 is an important regulator of the immune response in STS, functioning as a tumor suppressor and a modulator of response to PD-1 blockade. Its role in modulating chemokine expression and CD8 + T cell infiltration highlights its potential as a therapeutic target and predictive biomarker for STS immunotherapy.